Impact of innovations upon economic growth during recession - Snieska, Vytautas; Valodkiene, Gitana (Technological and Economic Development of Economy, 2015)
The role of the factors influencing economic growth during economic recessions and the role of these factors in separate economic phases are analysed. The purpose of the research is to assess the impact of innovations on economic growth during recession. The analysis of the situation in manufacturing sectors of Lithuania during economic recession in 2007 to 2009 has revealed several characteristics of innovations for this period due to which Lithuanian manufacturing enterprises managed to successfully function and remain competitive. The influence of household consumption expenditure on the growth of GDP in Lithuania is described by the function close to the linear, so we see a direct relation between these two variables. The influence of export on GDP is described by a convex function which has showed the declining influence of export on the GDP growth in the long-term perspective. Thus, contrary to a rather popular belief in transition countries, the main engine of growth in the long-term is not export. The long-term GDP growth is impossible without stimulating the growth in household consumption expenditure.